Definitely Maybe: New Governance of Uncertainty and Risk in Patient Group Involvement with UK Guidance on Testing for Lyme Disease. (March 2021) - Faulkner, Alex; Bloor, Kate; Hale, Vahsti
States that claim responsibility for citizens' healthcare try to deal with knowledge uncertainties while preserving a duty of care. Production of clinical guidelines in disputed medical conditions or where uncertainty is high, is difficult. Patient groups may advocate non-credentialed evidence, contribute to debates and form alliances with established policy actors. In this context, Lyme disease, especially highly contested 'chronic' Lyme disease is a good case with which to examine how official governance institutions are managing diagnostic uncertainty and evidence for tests. The healthcare state has been provoked to develop extensive policy for Lyme disease. In the UK, national Health Technology Assessment agency, NICE, began a consultation process in 2016. NICE and other policy actors are moving towards more participatory modes of decision-making. The article analyses NICE's recently published guidelines and consultation documents; patient groups' contributions; observations of consultations and of evidence review processes; and recent Department of Health systematic reviews, including patient group participation. We draw on concepts of participatory governance, patient group activism and guideline involvement. We find an increased level of participation by patient groups in recent policy and evidence review processes, and hence legitimation of them as 'stakeholders', alongside a strengthened state position on pre-existing diagnostic and testing standards.